Summing it up: An integrative review of studies of cancer survivorship care plans (2006‐2013). Issue 7 (23rd September 2014) - Mayer, Deborah K.; Birken, Sarah A.; Check, Devon K.; Chen, Ronald C.
<x xml:space="preserve">Abstract</x> In 2006, the Institute of Medicine recommended that cancer survivors who are completing primary treatment receive a survivorship care plan (SCP) based on face validity. The state of scientific knowledge regarding the SCP is unclear. The authors conducted an integrative review of existing evidence regarding SCPs. The MEDLINE/PubMed database, the Excerpta Medica Database (EMBASE), and the Cumulative Index to Nursing and Allied Health Literature (CINAHL) database were searched for relevant studies published between 2006 and 2013 using a combination of keywords: "survivors, " "survivorship, " "care plans, " "care planning, " "treatment summaries, " and "cancer." Articles were included if they 1) reported results from an empirical study, 2) included cancer survivors who were diagnosed at age ≥18 years, 3) related to SCP, and 4) were published in English. In total, 781 records were retrieved; 77 were identified as duplicates, and 665 were abstracts or presentations that did not relate to SCPs for adults or were not empirical, which left 42 articles for inclusion in this review. Studies regarding SCP fell into 3 categories: 1) content (n=14), 2) dissemination and implementation (n=14), and 3) survivor and provider outcomes (n=14). SCPs have been endorsed and are associated with improved knowledge, but SCP use remains sporadic. Only 4 studies were randomized controlled trials (RCTs) that avoided many biases associated with observational studies. Other limitations included cross‐sectional or pre‐SCP–post‐SCP ("pre‐post") designs, limited generalizability caused by a lack of sample diversity, and a lack of systematic testing of data‐collection tools. The quantity and quality of SCP research are limited. SCPs have been endorsed, but evidence of improved outcomes associated with SCP is limited. Future research that addresses the methodological concerns of extant studies is needed regarding SCP use, content, and outcomes. Cancer 2015;121:978–996. © 2014 American Cancer Society.